Flood hazard mapping of Jelai River, Pahang by integration HEC-RAS and ArcGIS software / Nur Ellisya Bahar - Bahar, Nur Ellisya (2023)
Floods were a type of natural disaster that causes massive property damage and death. Due to continuous rain and high tide, water overflowed to land and causing floods. The main goal of this study was to determine the flood recurrence to raise awareness and produce a map for flood event preparedness. Flood mapping was important because it will be helpful for preparing for upcoming flood events. It can serve as important guidelines for decision makers who want to make the best preparation for potential flood disaster in the future. In order to assist for preparedness, flood modelling was important because it can simulate real-world physic to provide hydrological parameters for damage modelling. The objectives of this study were to simulate the river’s water flow into the flood-prone area using HEC-RAS, to calculate the extent of the floodplains during the return period of interest and to generate the flood risk map using ArcGIS software. This study explains how the HEC-RAS model was used to create flood extent mapping of Jelai River in Lipis, Pahang. The analysis will use Digital Elevation Model (DEM), hydrological data and daily rainfall data. For flood frequency analysis, Log Pearson Type III used to calculate the peak flow of different return periods. The result from HECRAS analysis imported to ArcGIS to produce flood hazard maps for different return periods. The result from HEC-RAS analysis was imported to ArcGIS to produce flood maps for different return periods. These flood levels along the Jelai River’s side were 62.671, 63.359, 63.652 and 63.950 meter for return periods of 5, 25, 50 and 100 years, respectively. In general, this study found that flooded areas that was affected likely in low elevation places especially in the middle sections of the Jelai River.